Lietišķo e-pastu reģistra analīze - Moldavska, Jeļena (Latvijas Universitāte, 2016)
Mūsdienās elektroniskais pasts ir kļuvis par plaši izmantotu komunikācijas līdzekli uzņēmumos. Pētījuma mērķis bija noteikt lietišķo e-pastu reģistra izplatītākās iezīmes Latvijas azartspēļu uzņēmuma iekšējā un ārējā komunikācijā. Pētījumā tika izmantots Baibera un Konrāda (2009) reģistra analīzes modelis individuālajam e-pastam. Pētījuma rezultāti parādīja, ka lietišķajiem e-pastiem ir gan mutvārdu, gan rakstiskās diskursa īpašības. Lietišķo e-pastu izplatītākās iezīmes ir patstāvīgie darbības vārdi, lietvārdi, modālie darbības vārdi, personu vietniekvārdi, nozarē lietoti žargonismi un saīsinājumi. To lietojumu ietekmē situācijas konteksts , un to var sekmīgi pētīt, izmantojot Baibera un Konrāda (2009) reģistra analīzes modeli.

Electronic mail has become a means for frequent communication in companies. The goal of the study was to identify pervasive features of the register of business e-mails communicated in a gambling company in Latvia using the framework of register analysis of individual e-mails proposed by Biber and Conrad (2009). The results revealed that business e-mails comprise both the characteristics of spoken and written discourse due to its medium of communication.The pervasive linguistic features of the register of business e-mails communicated externally and internally are the use of lexical verbs, nouns, modal verbs, contracted forms, personal pronouns, specific jargon and abbreviations. They are affected by the situational characteristics, which can be discovered and analysed with the help of the “register analysis” proposed by Biber and Conrad (2009).
Register Analysis of Business E-mails
Keywords: Valodniecība; business e-mails; computer-mediated-discourse; business discourse; register analysis; pervasive linguistic features of e-mails